FINANCIAL BEHAVIOR OF BANK SYARIAH INDONESIA CUSTOMERS IN EAST KALIMANTAN: TRUST AS MEDIATION - Hidayani; Hairul Anwar; Doddy Adhimursandi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study seeks to examine the determinants that shape customers’ financial behavior, positioning trust as an intervening variable within the relationship. Three variables were selected: financial literacy, security perception, and financial inclusion. The endogenous variable is financial behavior. The sample of this study consists of 100 customers from PT Bank Syariah Indonesia (BSI) in East Kalimantan. Data were gathered through a questionnaire employing a purposive sampling approach, and subsequently analyzed using path analysis techniques. The findings indicate that financial inclusion exerts a positive and statistically significant impact on financial behavior. In contrast, financial literacy and security perception demonstrate a positive yet statistically non-significant influence on financial behavior. The three hypotheses regarding indirect effects, two have a significant positive impact: financial inclusion on financial behavior through trust and security perception on financial behavior through trust. These results demonstrate how important trust is as a mediating factor in determining financial behavior. Because these elements indirectly promote financial behavior through increased trust, the study's findings indicate that BSI East Kalimantan should prioritize increasing consumer perceptions of security and expanding financial inclusion. Customers may make more consistent financial decisions as a result of increased trust.